1995
DOI: 10.1182/blood.v86.3.1148.bloodjournal8631148
|View full text |Cite
|
Sign up to set email alerts
|

BCR-ABL-mediated inhibition of apoptosis with delay of G2/M transition after DNA damage: a mechanism of resistance to multiple anticancer agents

Abstract: A critical determinant of the efficacy of antineoplastic therapy is the response of malignant cells to DNA damage induced by anticancer agents. The p53 tumor-suppressor gene is a critical component of two distinct cellular responses to DNA damage, the induction of a reversible arrest at the G1/S cell cycle checkpoint, and the activation of apoptosis, a genetic program of autonomous cell death. Expression of the BCR-ABL chimeric gene produced by a balanced translocation in chronic myeloid leukemia, confers resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 0 publications
1
74
0
2
Order By: Relevance
“…Since all patients were under treatment, it is possible that this overexpression of TP53 may be a result of chemotherapyinduced DNA damage and inhibition of apoptosis in the cells downstream of TP53 induction. A recent study (Bedi et al, 1995) reported normal induction of TP53 and BCR-ABL mediated inhibition of apoptosis at the G 2 /M transition. We believe that TP53 accumulation may also affect this G 2 /M inhibition.…”
Section: Discussionmentioning
confidence: 97%
“…Since all patients were under treatment, it is possible that this overexpression of TP53 may be a result of chemotherapyinduced DNA damage and inhibition of apoptosis in the cells downstream of TP53 induction. A recent study (Bedi et al, 1995) reported normal induction of TP53 and BCR-ABL mediated inhibition of apoptosis at the G 2 /M transition. We believe that TP53 accumulation may also affect this G 2 /M inhibition.…”
Section: Discussionmentioning
confidence: 97%
“…Like to our results, they found only a limited amount of apoptosis. Inhibited apoptosis accompanied by G2/M delay after DNA damage is a possible mechanism of resistance to anticancer treatment (Bedi et al, 1995). G2/M delay may reflect time needed for DNA replication, chromosomal segregation and repair, in this way preventing cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Signals implicated in the antiapoptotic function of BCR-ABL include PI 3′ kinase/Akt [60,90], STAT5-dependent BCLXL upregulation [91] and NF-κB [92]. In addition, prolonged activation of the G 2 -specific cell cycle checkpoint via maintenance of inhibitory phosphorylation of CDC2 at tyrosine 15 has been ascribed directly to BCR-ABL, and shown to underlie its ability to suppress apoptosis and promote the long-term survival of hematopoietic cells following DNA damage [93,94].…”
Section: Antiapoptotic Signalsmentioning
confidence: 99%